2019
DOI: 10.1002/aur.2183
|View full text |Cite
|
Sign up to set email alerts
|

Implication of hypocholesterolemia in autism spectrum disorder and its associated comorbidities: A retrospective case–control study

Abstract: Autism spectrum disorder (ASD) has been associated with low cholesterol levels in a limited number of studies. However, the prevalence of hypocholesterolemia as well as the degree of association with ASD remains to be elucidated. We therefore sought to investigate the lipid profiles of a group of French‐Canadian ASD individuals. The medical records of 79 ASD individuals and 79 age and gender‐matched healthy controls were retrospectively reviewed. The fasting lipid profiles including total cholesterol (TC), hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 48 publications
2
15
0
Order By: Relevance
“…In addition, lower LRs cholesterol was associated with a higher score of autistic traits as evaluated by the SCQ questionnaire. These data agree with our previous report in ASD population that showed an increase of cognitive impairment risk when the plasma cholesterol is below the 10th centile of normalized population 45 . Taken together, these findings suggest a potential mechanistic implication of low cholesterol in cognitive dysfunction of FXS individuals probably through disruption of cholesterol content in LRs.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, lower LRs cholesterol was associated with a higher score of autistic traits as evaluated by the SCQ questionnaire. These data agree with our previous report in ASD population that showed an increase of cognitive impairment risk when the plasma cholesterol is below the 10th centile of normalized population 45 . Taken together, these findings suggest a potential mechanistic implication of low cholesterol in cognitive dysfunction of FXS individuals probably through disruption of cholesterol content in LRs.…”
Section: Discussionsupporting
confidence: 93%
“…The lower levels of cholesterol detected in PRRSVchallenged pigs relative to control gilts indicate that MIA may cause hypocholesterolemia. Serum hypocholesterolemia has been associated with autism spectrum disorder, a neurodevelopmental and behavioral disorder linked to MIA (Benachenhou et al, 2019).…”
Section: Effects Of Maternal Immune Activation On Metabolic Profilesmentioning
confidence: 99%
“…Moreover, a retrospective case-control study of a group of French-Canadian ASD individuals observed four times more hypocholesterolemia in ASD than in the general population [28]. Furthermore, low TC in ASD was associated with higher rates of ASD-associated intellectual disability and anxiety/depression [28]. These results suggest that decreased level of TC may be related to ASD.…”
Section: Discussionmentioning
confidence: 97%
“…Interestingly, a nested case-control study demonstrated that lower maternal postpartum plasma LDL concentration was associated with increased odds of ASD in offspring [27]. Moreover, a retrospective case-control study of a group of French-Canadian ASD individuals observed four times more hypocholesterolemia in ASD than in the general population [28]. Furthermore, low TC in ASD was associated with higher rates of ASD-associated intellectual disability and anxiety/depression [28].…”
Section: Discussionmentioning
confidence: 99%